A kind of high water-absorbent fiber for diaper core material and its production process
By using polyacrylamide microspheres and modified hydroxyethyl methacrylate in the diaper core layer material, combined with electrospinning and heat crosslinking technology, highly absorbent fibers were prepared, which solved the problem of poor bonding ability of polymer water-absorbing resin and fabrics in the prior art, significantly improved the liquid absorption ratio and fracture toughness, and improved the liquid absorption performance and service life of the diaper.
Patent Information
- Application Number
- CN202410586890.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-05-13
AI Technical Summary
The existing diaper absorbs the core layer material of the polymer water-absorbing resin and fabric have poor bonding ability, which leads to agglomeration of larger diameters easily after absorbing liquid, which reduces the liquid absorption rate and multiple liquid absorption capacity, and leads to damage to the structure of the diaper and uneven wear.
By using polyacrylamide microspheres and modified hydroxyethyl methacrylate in the diaper core layer material, combined with electrospinning and heat crosslinking processes, highly absorbent fibers were prepared to improve their water absorption ratio, salt resistance and fracture toughness.
It significantly improves the liquid absorption ratio and absorption speed of high-absorbent fibers, reduces the reverse osmosis amount, enhances the fracture toughness of the fibers, and improves the liquid absorption performance and service life of the diapers.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high water-absorbent fiber used for a core layer material of a diaper and a production process thereof. Background Art
[0002] With the rapid development of the diaper market, consumers have higher and higher requirements for diapers. As the key part of diapers, the absorbent core layer plays a role in absorbing and storing a large amount of urine. The performance of the core layer material directly affects the liquid absorption quality and usage time of the diaper.
[0003] The absorbent core layer of existing diapers mostly adopts a mixture of high molecular water-absorbent resin and fluff pulp. Although it has a large liquid absorption capacity and good side leakage prevention, the high molecular water-absorbent resin has poor bonding ability with the fabric and is not fixed in the fabric. After absorbing liquid, it is easy to form gel agglomerates with larger diameters, which not only reduces the liquid absorption rate and multiple liquid absorption capacity, but also causes damage to the diaper structure and makes it uneven when worn.
[0004] The existing technology mainly solves the problem of poor bonding ability with fabrics and instability in fabrics by making high-molecular water-absorbent resins into fibers. The fibrous high-absorbent material has a large surface area, fast water absorption rate and is soft, comfortable to contact with the skin, and the gel does not flow after absorbing water, which can maintain the original strength and integrity of the absorbent fiber, simplifying the manufacturing process of sanitary products.
[0005] Existing absorbent fibers are mainly divided into cellulose, polycarboxylic acid, polyacrylonitrile and modified polyvinyl alcohol. Among them, polycarboxylic acid absorbent fibers are the most produced and widely used. Homopolymers of monomers such as acrylic acid and butenoic acid or polymers obtained by copolymerization with acrylamide, acrylonitrile, styrene, etc. are commonly used raw materials for polycarboxylic acid absorbent fibers, but their slow water absorption rate and poor salt resistance limit their use. The existing technology can make the fiber have better water absorption rate and salt resistance by introducing multiple hydrophilic groups, but the water absorption rate is low. In addition, the resin after surface cross-linking is improved in salt resistance and gel strength, but it also leads to a decrease in water absorption rate. At the same time, the existing absorbent fibers have poor toughness and are prone to breakage. Summary of the invention
[0006] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a super absorbent fiber for the core material of diapers and its production process, and to improve the water absorption rate, salt resistance and fracture toughness of the super absorbent fiber by adding polyacrylamide microspheres and modified hydroxyethyl methacrylate.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A highly absorbent fiber for a core material of a diaper, comprising the following raw materials in parts by weight: 70-90 parts of sodium acrylate solution, 20-45 parts of polyacrylamide microspheres, 2-10 parts of modified hydroxyethyl methacrylate, 10-30 parts of polyvinyl alcohol solution, 0.5-5 parts of an initiator, and 1-5 parts of a crosslinking agent; the polyacrylamide microspheres are polyacrylamide microspheres prepared by reverse suspension polymerization; the modified hydroxyethyl methacrylate is hydroxyethyl methacrylate modified by grafting oxidized multi-walled carbon nanotubes with hydroxyethyl methacrylate.
[0009] Preferably, the mass concentration of the polyvinyl alcohol solution is 10-20%; the initiator is one of potassium persulfate and ammonium persulfate; and the cross-linking agent is one of N,N-dimethylenebisacrylamide and glutaraldehyde.
[0010] Preferably, the method for preparing the sodium acrylate solution comprises the following steps: placing acrylic acid in a water bath at 10-30° C., adding a sodium hydroxide solution with a mass concentration of 20-30% to neutralize the acrylic acid, and preparing the sodium acrylate solution.
[0011] Preferably, the mass ratio of the acrylic acid to the sodium hydroxide solution is 1:1-2.
[0012] Preferably, the method for preparing the polyacrylamide microspheres comprises the following steps:
[0013] (1) dissolving acrylamide, N,N-dimethylenebisacrylamide and ammonium persulfate in deionized water to obtain an aqueous phase, dissolving sorbitan monolaurate in cyclohexane and performing ultrasonic dispersion to obtain an oil phase;
[0014] (2) The oil phase is placed in a reactor, and stirred in an oil bath at 30-45°C under a nitrogen atmosphere. The obtained aqueous phase is then added dropwise to the reactor, and the temperature is raised to 60-75°C for reaction for 1-3 hours. The temperature is then lowered to 40-50°C and kept warm for 40-60 minutes. After the temperature drops to room temperature, the reaction product is slowly poured into anhydrous ethanol to produce precipitation, and the precipitation is centrifuged, washed, and dried to prepare polyacrylamide microspheres.
[0015] Preferably, in step (1), the mass ratio of acrylamide, N,N-dimethylenebisacrylamide, ammonium persulfate and sorbitan monolaurate is 5: 0.03-0.07: 0.05-0.1: 1-1.5.
[0016] Preferably, the preparation method of the modified hydroxyethyl methacrylate comprises the following steps:
[0017] A. Place multi-walled carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1, perform ultrasonic oscillation at room temperature for 20 to 30 minutes, stir in an oil bath at 75 to 90°C for 4 to 6 hours, filter and wash the product until it is neutral, and vacuum dry it to obtain oxidized multi-walled carbon nanotubes;
[0018] B. Place isophorone diisocyanate in a reactor, add anhydrous butyl acetate and stir evenly, then add dibutyltin dilaurate, raise the temperature to 35-50° C., then dropwise add hydroxyethyl methacrylate, react for 5-6 hours, and prepare isocyanato hydroxyethyl methacrylate;
[0019] C. Take oxidized multi-walled carbon nanotubes in anhydrous butyl acetate, ultrasonically disperse them at 25-40°C, transfer them to a reactor, heat them to 55-80°C, add dibutyltin dilaurate, mix isocyanato hydroxyethyl methacrylate and anhydrous butyl acetate evenly, add them to the reactor, react at a constant temperature for 10-12h, filter after the reaction is completed, wash and dry to prepare modified hydroxyethyl methacrylate.
[0020] Preferably, in step B, the mass ratio of isophorone diisocyanate, dibutyltin dilaurate and hydroxyethyl methacrylate is 10:0.02-0.05:5.5-8.
[0021] Preferably, in step C, the mass ratio of oxidized multi-walled carbon nanotubes, dibutyltin dilaurate and isocyanato hydroxyethyl methacrylate is 3-7:0.01-0.05:6-15.
[0022] The production process of the super absorbent fiber used for the core material of diapers as described above comprises the following steps:
[0023] S1. Weigh the raw materials according to weight, mix the sodium acrylate solution and the modified hydroxyethyl methacrylate, and then add the polyvinyl alcohol solution and the initiator to obtain a mixed solution;
[0024] S2, placing the mixed solution at 40-80° C. for polymerization reaction, cooling, and obtaining a polymerization solution;
[0025] S3, adding polyacrylamide microspheres and a cross-linking agent to the polymer solution, and performing a degassing treatment to obtain a spinning solution;
[0026] S4, subjecting the spinning solution to electrospinning and thermal crosslinking treatment to obtain the highly absorbent fiber for the core material of the diaper
[0027] Beneficial effects of the present invention:
[0028] The invention utilizes partially neutralized acrylic acid and modified hydroxyethyl methacrylate to undergo copolymerization, adds polyvinyl alcohol solution for blending, and then adds polyacrylamide microspheres, an initiator, and a crosslinking agent to prepare a spinning solution, uses an electrostatic spinning technology to prepare primary nanofibers, and then undergoes heat treatment to obtain highly absorbent fibers. Since acrylic acid and modified hydroxyethyl methacrylate contain a large number of hydrophilic groups, self-acceleration occurs during the reaction, resulting in cross-linking between molecules, and easily causing explosion polymerization to generate a gel-like substance. The generated polymer solution has poor spinnability. The addition of polyvinyl alcohol slows down the self-acceleration phenomenon while improving the spinnability of the polymer solution.
[0029] The invention uses acrylamide as a monomer, ammonium persulfate as an initiator, N,N-dimethylenebisacrylamide as a crosslinking agent, and sorbitan monolaurate as a dispersant, and utilizes an inverse suspension polymerization method to prepare polyacrylamide microspheres, which have a higher water absorption rate and better water storage performance. In addition, the present invention utilizes concentrated sulfuric acid and concentrated nitric acid to oxidize multi-walled carbon nanotubes, and the surfaces of the oxidized multi-walled carbon nanotubes are rich in hydroxyl groups and carboxyl groups. At the same time, the present invention utilizes the isocyanate groups with high reaction activity directly connected to the cyclohexane ring in isophorone diisocyanate to react with the hydroxyl groups on the surface of hydroxyethyl methacrylate, and the hydroxyethyl methacrylate semi-closes the isophorone diisocyanate, and then utilizes another isocyanate group in isophorone diisocyanate to react with the hydroxyl groups on the surface of the oxidized multi-walled carbon nanotubes to prepare modified hydroxyethyl methacrylate, thereby introducing double bonds on the surfaces of the oxidized multi-walled carbon nanotubes as a bridge for polymerization with acrylic acid, and at the same time being beneficial to the dispersion of the multi-walled carbon nanotubes in the polymer, wherein the oxidized multi-walled carbon nanotubes have a large specific surface area and a high porosity, and the surface contains abundant functional groups and active points, and the interaction force between the oxidized multi-walled carbon nanotubes and the water molecules is strong, thereby improving the water absorption rate and salt resistance of the water-absorbing fiber, and at the same time improving the fracture toughness of the water-absorbing fiber. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1 A method for preparing a sodium acrylate solution comprises the following steps:
[0032] 21 g of acrylic acid was placed in a 30° C. water bath, and 28 g of a 20% mass concentration sodium hydroxide solution was added for neutralization to prepare a sodium acrylate solution.
[0033] Embodiment 2 A method for preparing polyacrylamide microspheres comprises the following steps:
[0034] (1) 5 g of acrylamide, 0.03 g of N,N-dimethylenebisacrylamide and 0.07 g of ammonium persulfate were dissolved in 100 mL of deionized water to obtain an aqueous phase, and 1.2 g of sorbitan monolaurate was dissolved in 100 mL of cyclohexane and dispersed by ultrasonication to obtain an oil phase;
[0035] (2) The oil phase is placed in a reactor and stirred in a 30°C oil bath under a nitrogen atmosphere. The obtained aqueous phase is then added dropwise to the reactor. The temperature is raised to 65°C for reaction for 2 hours. The temperature is then lowered to 45°C and kept warm for 60 minutes. After the temperature drops to room temperature, the reaction product is slowly poured into anhydrous ethanol to produce a precipitate. The product is then centrifuged, washed, and dried to prepare polyacrylamide microspheres.
[0036] Embodiment 3 A method for preparing modified hydroxyethyl methacrylate comprises the following steps:
[0037] A. 3 g of multi-walled carbon nanotubes were placed in 118 mL of a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and ultrasonically shaken at room temperature for 25 min. The mixture was stirred in an oil bath at 80°C for 6 h. The product was filtered and washed until neutral, and vacuum dried to obtain oxidized multi-walled carbon nanotubes.
[0038] B. Take 10g of isophorone diisocyanate and place it in a reactor, add 50mL of anhydrous butyl acetate and stir evenly, then add 0.03g of dibutyltin dilaurate, raise the temperature to 45°C, then dropwise add 5.8g of hydroxyethyl methacrylate, react for 5.5h, and prepare isocyanato hydroxyethyl methacrylate;
[0039] C. Take 3g of oxidized multi-walled carbon nanotubes in 50mL of anhydrous butyl acetate, transfer to a reactor after ultrasonic dispersion at 30°C, heat to 70°C, add 0.01g of dibutyltin dilaurate, take 8g of isocyanate hydroxyethyl methacrylate and 10mL of anhydrous butyl acetate, mix well and add to the reactor, react at constant temperature for 11h, filter after the reaction is completed, wash and dry to prepare modified hydroxyethyl methacrylate.
[0040] Example 4 A highly absorbent fiber for a diaper core material comprises the following raw materials in parts by weight: 70 parts of sodium acrylate solution, 22 parts of polyacrylamide microspheres, 2 parts of modified hydroxyethyl methacrylate, 10 parts of 10% mass concentration polyvinyl alcohol solution, 1 part of initiator potassium persulfate, and 2 parts of cross-linking agent glutaraldehyde.
[0041] The production process of the super absorbent fiber used for the core material of diapers comprises the following steps:
[0042] S1. Weigh the raw materials according to weight, mix the sodium acrylate solution and the modified hydroxyethyl methacrylate, and then add the polyvinyl alcohol solution and the initiator to obtain a mixed solution;
[0043] S2, placing the mixed solution at 60° C. for polymerization reaction, cooling, and obtaining a polymerization solution;
[0044] S3, adding polyacrylamide microspheres and a cross-linking agent to the polymer solution, and performing a degassing treatment to obtain a spinning solution;
[0045] S4. Place the spinning solution in an electrospinning machine, set the voltage to 30 kV, adjust the distance between the nozzle and the receiving roller to 15 cm, perform electrospinning to obtain spun fibers, place the spun fibers under thermal crosslinking treatment at 140° C. for 120 min, and obtain highly absorbent fibers.
[0046] Example 5 A highly absorbent fiber for a diaper core material comprises the following raw materials in parts by weight: 75 parts of sodium acrylate solution, 30 parts of polyacrylamide microspheres, 5 parts of modified hydroxyethyl methacrylate, 25 parts of 20% mass concentration polyvinyl alcohol solution, 2 parts of initiator potassium persulfate, and 3 parts of cross-linking agent glutaraldehyde.
[0047] The production process of the super absorbent fiber used for the core material of diapers is the same as that of Example 4.
[0048] Example 6 A highly absorbent fiber for a diaper core material comprises the following raw materials in parts by weight: 90 parts of sodium acrylate solution, 45 parts of polyacrylamide microspheres, 8 parts of modified hydroxyethyl methacrylate, 30 parts of 10% mass concentration polyvinyl alcohol solution, 4 parts of initiator potassium persulfate, and 5 parts of cross-linking agent glutaraldehyde.
[0049] The production process of the super absorbent fiber used for the core material of diapers is the same as that of Example 4.
[0050] Comparative Example 1 A highly absorbent fiber for a diaper core material comprises the following raw materials in parts by weight: 78 parts of sodium acrylate solution, 36 parts of acrylamide, 7 parts of modified hydroxyethyl methacrylate, 25 parts of 10% mass concentration polyvinyl alcohol solution, 2 parts of initiator potassium persulfate, and 4 parts of cross-linking agent glutaraldehyde.
[0051] The production process of the super absorbent fiber used for the core material of diapers comprises the following steps:
[0052] S1. Weigh the raw materials in parts by weight, mix the sodium acrylate solution, acrylamide and modified hydroxyethyl methacrylate, and then add the polyvinyl alcohol solution and initiator to obtain a mixed solution;
[0053] S2, placing the mixed solution at 60° C. for polymerization reaction, cooling, and obtaining a polymerization solution;
[0054] S3, adding a cross-linking agent to the polymer solution, and performing a degassing treatment to obtain a spinning solution;
[0055] S4. Place the spinning solution in an electrospinning machine, set the voltage to 30 kV, adjust the distance between the nozzle and the receiving roller to 15 cm, perform electrospinning to obtain spun fibers, place the spun fibers under thermal crosslinking treatment at 140° C. for 120 min, and obtain highly absorbent fibers.
[0056] Comparative Example 2 A highly absorbent fiber for the core material of a diaper comprises the following raw materials in parts by weight: 80 parts of sodium acrylate solution, 38 parts of polyacrylamide microspheres, 10 parts of hydroxyethyl methacrylate, 15 parts of 10% mass concentration polyvinyl alcohol solution, 3 parts of initiator potassium persulfate, and 3 parts of cross-linking agent glutaraldehyde.
[0057] The production process of the super absorbent fiber used for the core material of diapers comprises the following steps:
[0058] S1, weighing the raw materials according to weight, mixing the sodium acrylate solution and hydroxyethyl methacrylate, and then adding the polyvinyl alcohol solution and the initiator to obtain a mixed solution;
[0059] S2, placing the mixed solution at 60° C. for polymerization reaction, cooling, and obtaining a polymerization solution;
[0060] S3, adding polyacrylamide microspheres and a cross-linking agent to the polymer solution, and performing a degassing treatment to obtain a spinning solution;
[0061] S4. Place the spinning solution in an electrospinning machine, set the voltage to 30 kV, adjust the distance between the nozzle and the receiving roller to 15 cm, perform electrospinning to obtain spun fibers, place the spun fibers under thermal crosslinking treatment at 140° C. for 120 min, and obtain highly absorbent fibers.
[0062] Performance Testing
[0063] The performance of the highly absorbent fibers prepared in Examples 4-6 and Comparative Examples 1-2 was tested:
[0064] (1) Water absorption rate test: Use the tea bag method, weigh 1g of super absorbent fiber and put it into a tea bag, immerse it in deionized water (0.9% saline), and when the liquid is fully absorbed and reaches equilibrium, hang it and let it stand for 30 minutes to remove the unabsorbed water (saline), and then weigh the mass of the super absorbent fiber. The water absorption rate is calculated by Q = (m 1 -m 2 ) / m 2 The formula is used for calculation, where m 1 is the mass of the super absorbent fiber after absorbing liquid, m 2 The arithmetic mean of the three determination results is taken as the determination result, and the data results are shown in Table 1.
[0065] (2) Absorption rate test: Take 50 mL of deionized water in a beaker, put a magnetic rotor in the beaker, place it on a magnetic stirrer, adjust the speed to 600 r / min, add 2 g of super absorbent fiber and pour it into the vortex. While absorbing deionized water, the vortex begins to disappear. The time required for the liquid surface to reach a stationary state is measured as the absorption rate. The data results are shown in Table 1.
[0066] (3) Reverse osmosis test: After absorbing deionized water for 1 hour, place the super absorbent fiber at 25°C and 70% (relative humidity). Place a piece of filter paper on its surface and record the mass in m. 1 , press with a 250g weight for 6h, and weigh the filter paper after 6h. 2 , calculate the reverse osmosis volume as m 2 -m 1 The data results are shown in Table 1.
[0067] (4) Tensile strength test: Weigh 10 g of super absorbent fiber and clamp it on the tensile testing machine. Click the start switch and record the value when the fiber breaks, which is the tensile strength. The data results are shown in Table 1.
[0068] Table 1 Sample performance test results
[0069]
[0070] As can be seen from the data in Table 1, the highly absorbent fibers prepared in Examples 4-6 of the present invention have high liquid absorption rate, fast absorption speed, low reverse osmosis amount, excellent water absorption and retention performance, high tensile strength, good toughness, and are not easy to break. In Comparative Example 1, polyacrylamide microspheres are replaced with acrylamide components, and hydroxyethyl methacrylate is not modified in Comparative Example 2. The liquid absorption rate, absorption speed, and reverse osmosis amount measured in Comparative Examples 1-2 are all worse than those in Examples 4-6, wherein the addition of polyacrylamide microspheres can significantly increase the liquid absorption rate of the fiber and reduce the reverse osmosis amount, and the addition of modified hydroxyethyl methacrylate can significantly increase the liquid absorption rate, salt resistance, and tensile strength of the fiber.
[0071] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0072] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A super absorbent fiber for a core material of a diaper, characterized in that: The invention comprises the following raw materials in parts by weight: 70-90 parts of sodium acrylate solution, 20-45 parts of polyacrylamide microspheres, 2-10 parts of modified hydroxyethyl methacrylate, 10-30 parts of polyvinyl alcohol solution, 0.5-5 parts of initiator, and 1-5 parts of crosslinking agent; the polyacrylamide microspheres are polyacrylamide microspheres prepared by reverse suspension polymerization; the modified hydroxyethyl methacrylate is hydroxyethyl methacrylate grafted with oxidized multi-walled carbon nanotubes to modify hydroxyethyl methacrylate; The preparation method of the modified hydroxyethyl methacrylate comprises the following steps: A. Place multi-walled carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1, perform ultrasonic oscillation at room temperature for 20 to 30 minutes, stir in an oil bath at 75 to 90°C for 4 to 6 hours, filter and wash the product until it is neutral, and vacuum dry it to obtain oxidized multi-walled carbon nanotubes; B. Place isophorone diisocyanate in a reactor, add anhydrous butyl acetate and stir evenly, then add dibutyltin dilaurate, raise the temperature to 35-50° C., then dropwise add hydroxyethyl methacrylate, react for 5-6 hours, and prepare isocyanato hydroxyethyl methacrylate; C. Take oxidized multi-walled carbon nanotubes in anhydrous butyl acetate, disperse them by ultrasonic at 25-40° C., transfer them to a reactor, heat them to 55-80° C., add dibutyltin dilaurate, mix isocyanato hydroxyethyl methacrylate and anhydrous butyl acetate evenly, add them to the reactor, react at a constant temperature for 10-12 hours, filter after the reaction is completed, wash and dry, and prepare modified hydroxyethyl methacrylate; The production process of the super absorbent fiber comprises the following steps: S1. Weigh the raw materials according to weight, mix the sodium acrylate solution and modified hydroxyethyl methacrylate, and then add the polyvinyl alcohol solution and the initiator to obtain a mixed solution; S2, placing the mixed solution at 40-80° C. for polymerization reaction, cooling, and obtaining a polymerization solution; S3, adding polyacrylamide microspheres and a cross-linking agent to the polymer solution, and performing a degassing treatment to obtain a spinning solution; S4, subjecting the spinning solution to electrospinning and thermal cross-linking treatment to obtain the highly absorbent fiber used for the core material of diapers.
2. The super absorbent fiber for the core material of diapers according to claim 1, characterized in that: The mass concentration of the polyvinyl alcohol solution is 10-20%; the initiator is one of potassium persulfate and ammonium persulfate; and the cross-linking agent is one of N,N-dimethylenebisacrylamide and glutaraldehyde.
3. The super absorbent fiber for the core material of diapers according to claim 1, characterized in that: The method for preparing the sodium acrylate solution comprises the following steps: placing acrylic acid in a water bath at 10-30° C., adding a sodium hydroxide solution with a mass concentration of 20-30% to neutralize the acrylic acid, and preparing the sodium acrylate solution.
4. The super absorbent fiber for the core material of diapers according to claim 3, characterized in that: The mass ratio of the acrylic acid to the sodium hydroxide solution is 1:1-2.
5. The super absorbent fiber for the core material of diapers according to claim 1, characterized in that: The preparation method of the polyacrylamide microspheres comprises the following steps: (1) dissolving acrylamide, N,N-dimethylenebisacrylamide and ammonium persulfate in deionized water to obtain an aqueous phase, dissolving sorbitan monolaurate in cyclohexane and performing ultrasonic dispersion to obtain an oil phase; (2) The oil phase is placed in a reactor, and stirred in an oil bath at 30-45°C under a nitrogen atmosphere. The obtained aqueous phase is then added dropwise to the reactor, and the temperature is raised to 60-75°C for reaction for 1-3 hours. The temperature is then lowered to 40-50°C and kept warm for 40-60 minutes. After the temperature drops to room temperature, the reaction product is slowly poured into anhydrous ethanol to produce precipitation, and the precipitation is centrifuged, washed, and dried to prepare polyacrylamide microspheres.
6. The super absorbent fiber for the core material of diapers according to claim 5, characterized in that: In the step (1), the mass ratio of acrylamide, N,N-dimethylenebisacrylamide, ammonium persulfate and sorbitan monolaurate is 5: 0.03-0.07: 0.05-0.1: 1-1.
5.
7. The super absorbent fiber for the core material of diapers according to claim 1, characterized in that: In the step B, the mass ratio of isophorone diisocyanate, dibutyltin dilaurate and hydroxyethyl methacrylate is 10:0.02-0.05:5.5-8.
8. The super absorbent fiber for the core material of diapers according to claim 1, characterized in that: In the step C, the mass ratio of oxidized multi-walled carbon nanotubes, dibutyltin dilaurate and isocyanato hydroxyethyl methacrylate is 3-7:0.01-0.05:6-15.
Citation Information
Patent Citations
Preparation method of fiber with high water absorption
CN103160952A
Composition for preparing water-absorbent resin fiber, water-absorbent resin fiber and preparation method of water-absorbent resin fiber
CN116854857A
Cited By
Preparation method of chitosan-based superabsorbent material with antibacterial function and application thereof to sanitary napkins
CN120396452B